Musical Illustration in the Film Silogui: A Cinematic Study of Mentawai Children - Martiano, Vereki; Zaidi, Ahmad; Askhan, Asifa; Putra, Andika Bayu (Institut Seni Indonesia Padangpanjang, 2025)
ABSTRACT The film